To subtract \( 4.66 \times 10^{-5} - 7.34 \times 10^{-7} \), we first need to write both numbers with the same exponent.
The number \( 4.66 \times 10^{-5} \) can be rewritten as: \[ 4.66 \times 10^{-5} = 4.66 \times 10^{-5} = 4.66 \times 10^{-5} \quad \text{(no change)} \]
Now, to convert \( 7.34 \times 10^{-7} \) to the same exponent, we can express it as: \[ 7.34 \times 10^{-7} = 0.0734 \times 10^{-5} \]
Now, we can subtract: \[ 4.66 \times 10^{-5} - 0.0734 \times 10^{-5} = (4.66 - 0.0734) \times 10^{-5} = 4.5866 \times 10^{-5} \]
Thus, the result is: \[ 4.5866 \times 10^{-5} \]
The correct answer is: 4.5866×10−5 (4.5866 times 10 to the power of negative 5).